(untitled) (International Journal of Agricultural Research, Innovation and Technology, 2016)
This paper aimed to assess the involvement of child labour in agribusinesses as well as the schooling pattern of children involved in these agribusinesses in Cameroon. For this study, some descriptive statistics and cross tabulations were computed using SPSS.20 and stata 13 software packages. The population of this study was made up of 51,190 individuals of both sexes that were concerned by the third Cameroon National Household Survey. The sample drawn from this population was constituted of individuals of age 5-17 years old, making a total of 17,550 children. The main results of this study revealed that agribusiness child labour was present everywhere in Cameroon and by both boys and girls. Children of all ages of the sample were concerned by the phenomenon and their level of education was essentially the primary. The impact of agribusiness child labour on education was positive because it helped the working and schooling children to provide means to finance their education and other needs. On the other hand, it has a negative impact on education because some children went for these jobs and finally stayed there and did not return back to school. Int. J. Agril. Res. Innov. & Tech. 5 (2): 58-63, December, 2015